Preliminary study on biological treatment of polychlorinated biphenyls (PCBs) using biofilm acclimatized in an anaerobic environment - Lizardo, Allan M. (Animo Repository, 2005)
The use of the biofilms is a promising technology for the treatment of hazardous and toxic wastes. In this study, biofilms are grown aerobically, acclimatized to anaerobic environment and used to degrade polychlorinated biphenlyls (PCBs).Biofilms are grown aerobically in three-phase fluidized bed reactor using cement balls made from content. The time course of biomass growth was monitored by conducting batch test for mixed liquor volatile solids (MLVS) and chemical oxygen demand (COD) every week.Batch experiments were carried out using 250 ml flasks containing anaerobic medium and 15 ml of the grown biofilms. Bioreactors were incubated with agitation at 28-30oC. The time course of the acclimatization of biofilm to anaerobic condition was determined bhy measuring the chemical oxygen demand (COD) eveyday until it reach steady state. Batch acclimatization of anaerobic biofilms to PCBs was monitored by conducting degradation test until results reached steady state.Preliminary results show that in the acclimatization of biofilms to anaerobic environment, 43% reduction in COD was attained after 11 days, and 71.54% reduction in concentration of PCB after 44 days.